Poverty Imputation in Contexts without Consumption Data: A Revisit with Further Refinements - Hai-Anh Dang; Talip Kilic; Kseniya Abanokova; Calogero Carletto (Institute of Labor Economics (IZA), 2023)
Household consumption data are often unavailable, not fully collected, or incomparable over time in poorer countries. Survey-to-survey imputation has been increasingly employed to address these data gaps for poverty measurement, but its effective use requires standardized protocols. We refine existing poverty imputation models using 14 multi-topic household surveys conducted over the past decade in Ethiopia, Malawi, Nigeria, Tanzania, and Vietnam. We find that adding household utility expenditures to a basic imputation model with household-level demographic and employment variables provides accurate estimates, which even fall within one standard error of the true poverty rates in many cases. Further adding geospatial variables improves accuracy, as does including additional community-level predictors (available from data in Vietnam) related to educational achievement, poverty, and asset wealth. Yet, within-country spatial heterogeneity exists, with certain models performing well for either urban areas or rural areas only. These results offer cost-saving inputs into future survey design.
Keywords: C15; I32; O15; 330; consumption; poverty; survey-to-survey imputation; household surveys; Vietnam; Ethiopia; Malawi; Nigeria; Tanzania; Sub-Saharan Africa